2019
DOI: 10.1080/13683500.2019.1645096
|View full text |Cite
|
Sign up to set email alerts
|

Analysing trends in the spatio-temporal behaviour patterns of mainland Chinese tourists and residents in Hong Kong based on Weibo data

Abstract: Visiting tourists and residents of a city interact at various locations at various times. Previous studies paid little attention to comparing the spatio-temporal behaviours of tourists and residents from a long-term perspective. The aim of the present study was to identify and compare the spatio-temporal behaviours of mainland Chinese tourists and residents in Hong Kong over a period of five years. Their behaviours were compared by means of kernel density analysis and temporal statistical analysis, using Weibo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 56 publications
0
28
0
Order By: Relevance
“…In most cases, tourists and residents are not set apart and rather increasingly share the same venues and facilities within a city [36], which can be observed by analyzing and comparing the spatiotemporal patterns of both groups in the city. In order to better compare the spatiotemporal patterns, it is important to discuss the temporal and spatial patterns as well as the nature of the places where the tourists and residents may interact [37]. Gu et al [29] identified resident and non-resident areas from the location of the registered user ID to find the origins of social media users.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In most cases, tourists and residents are not set apart and rather increasingly share the same venues and facilities within a city [36], which can be observed by analyzing and comparing the spatiotemporal patterns of both groups in the city. In order to better compare the spatiotemporal patterns, it is important to discuss the temporal and spatial patterns as well as the nature of the places where the tourists and residents may interact [37]. Gu et al [29] identified resident and non-resident areas from the location of the registered user ID to find the origins of social media users.…”
Section: Related Workmentioning
confidence: 99%
“…Paldino et al [13] and Kotus et al [4] also confirmed that tourists are more active in central areas of the city, whereas residents are active in socializing places like squares, parks, and sports facilities, by comparing both the tourists' and residents' data. In urban tourism, the activities of tourists and residents are not only unevenly distributed in space, but also in time [37,39]. Li et al [40] presented the uneven distribution in days-, weeks-, and holidays-related differences of the Chinese tourist activities in Lijiang.…”
Section: Related Workmentioning
confidence: 99%
“…Assurance is demonstrated through hotel staff skills and competence, courteousness, and ability to inspire trust and confidence in the guests being serviced (Fredrick 2019;Shahin et al 2010;Shahin et al 2006;Parasuraman et al 1985). Studies on hospitality found that service assurance for hotels significantly influences customer perception (Su et al 2020;Aguiar-Quintana et al 2016;Lam and Zhang 1999). Additionally, travelers who are involved in health care also demand more protection when they receive services (Manna et al 2020;Collins et al 2019;Pan and Moreira 2018;Drinkert and Singh 2017).…”
Section: Assurancementioning
confidence: 99%
“…Previous studies report that tourists and residents have distinct expectations and attitudes towards the product or service they purchased, which results in different behaviours (Lloyd et al, 2011;Su, Spierings, Dijst, & Tong, 2019). Shopping destinations classify tourists and residents into two different groups with distinct explanations for each group for shopping.…”
Section: Tourist and Resident As Destination Stakeholdersmentioning
confidence: 99%